Influence of Product Quality Differentiation Strategies on Client Sustenance in Barclays Bank-Kisii Branch, Kenya - Ochwangi Mengo; Dr. Simon Nyakwara (IJRDO - Journal of Business Management, 2020)
The necessity to remain competitive as a result of changes in clients’ needs has been a key preserve of most banks where as a service industry, launching and enhancing new products and services is a clear way of retaining and attracting new customers. Thus, the purpose of the study was to assess the influence of differentiation strategies on client sustenance in banking industry in Barclays Bank-Kisii Branch, Kenya. The study adopted a descriptive survey research design with a target population of 30 employees of the Barclays bank Kisii branch. The researcher collected data using questionnaires, interviews, observation and document analysis. The study established that product quality, design and development, product innovation, brand differentiation positively and significantly influence clients’ sustainability. The study recommends that in order to enhance clients’ sustainability, the banks should put in place product quality differentiation strategies in terms of Features, Reliability, Procedures and Serviceability, put in place design and development differentiation strategies in terms of Product look, Functionality, Aesthetic and Feels, put in place product innovations differentiation strategies in terms of technology, research, and New products development and put in place brand differentiation strategies in terms of brand name, Strong brand identification, Brand quality and Brand design